Diagnóstico de Gestação em Fêmeas Bovinas. - Neto, Paulo Sabino Milhomem (Universidade Federal do Tocantins, 2023)
The supervised curricular traineeship was carried out from August 10, 2017 to October 27, 2017 for a total of 345 hours, supervised by veterinarian Danilo Pincinato and counselor Prof. Dr. Jorge Ferreira. The internship was carried out at the company CLIVAR Reprodução Bovina, a service provider and consultant in the areas of breeding and production of cattle, serving farms throughout the state of Tocantins. The compulsory curricular traineeship is extremely important for the training of any professional, since it was essential to complement the knowledge acquired during graduation within a reality of professional and practical challenges.